Development of Hospital Perception Scale for Healthy Children (HPSHC) and Investigation of Its Psychometric Properties - Behice Ekici (MDPI AG, 2023)
(1) Aim: The aim of the study was to develop and analyze the psychometric properties of a hospital perception scale for healthy children aged 8 to 10 years. (2) Methods: A methodological design was employed. The scale's validity was investigated using the approaches of content validity, face validity, item analysis, and construct validity. The scale's reliability was evaluated utilizing the approaches of internal consistency reliability, measurer reliability, and measurement invariance. (3) Results: In total, 330 children took part in this study. The scale is composed of six factors. Factor loads range from 0.42 to 0.79. The item-total score correlation coefficients were 0.42 and 0.79, respectively, while the Cronbach alpha reliability coefficient was 0.87. (4) Conclusions: The HPSHC is a valid and reliable tool. It can be used to determine how healthy or sick children in their middle childhood are perceived when going to the hospital and being hospitalized.